An exploratory study on information retention in social media platforms among Generation Y. (2018) - Abhijith, U.; Rejikumar, G.
This study was designed to analyse the effect of antecedents which contribute to higher degrees of information retention and sharing intention across various social media platforms under information overload. A cross-sectional study, where perceptions of 256 Y gen respondents were collected using a structured questionnaire circulated online across India. Constructs used in the study were conceptualised as reflective and variance based structural equation modelling (SEM) analysis was used to test the theory. The study found that social media trust perceived by a user lead to higher retention of the contents generated by firms across platforms but the intervention of information overload degrades the retention and sharing intentions. The study concluded that information overload is not controllable and therefore the indicators which lead to social media trust has to be identified and improved by the marketers and content generators for higher rate of retention and sharing intentions across platforms.